Pengaruh Komunikasi Dalam Penganggaran Dan Motivasi Terhadap Kinerja Manajer Perkebunan Pada PT Perkebunan Nusantara II - Hutagalung, Galumbang (Jurnal Manajemen Dan Akuntansi Medan, 2022)
The purpose of this study is to examine the impact of budget communication and motivation with performance. A survey method was conducted on 179 managers involved in budgetary process in plantation industry in North Sumatera using self-administered structured questionnaire. The finding support the postulation that budgetary communication, intrinsic motivation, and extrinsic motivation significantly and positively influenced plantation managers’ performance